Acoustic Correlates and Adult Perceptions of Distress in Infant Speech-Like Vocalizations and Cries - Yoo, Hyunjoo; Buder, Eugene H.; Bowman, Dale D.; Bidelman, Gavin M.; Oller, D. Kimbrough (Frontiers in Psychology, 2019)
Prior research has not evaluated acoustic features contributing to perception of human infant vocal distress or lack thereof on a continuum. The present research evaluates perception of infant vocalizations along a continuum ranging from the most prototypical intensely distressful cry sounds (“wails”) to the most prototypical of infant sounds that typically express no distress (non-distress “vocants”). Wails are deemed little if at all related to speech while vocants are taken to be clear precursors to speech. We selected prototypical exemplars of utterances representing the whole continuum from 0 and 1 month-olds. In this initial study of the continuum, our goals are to determine 1) listener agreement on level of vocal distress across the continuum, 2) acoustic parameters predicting ratings of distress, 3) the extent to which individual listeners maintain or change their acoustic criteria for distress judgments across the study, 4) the extent to which different listeners use similar or different acoustic criteria to make judgments, and 5) the role of short-term experience among the listeners in judgments of infant vocalization distress. Results indicated that 1) both inter-rater and intra-rater listener agreement on degree of vocal distress was high, 2) the best predictors of vocal distress were number of vibratory regimes within utterances, utterance duration, spectral ratio (spectral concentration) in vibratory regimes within utterances, and mean pitch, 3) individual listeners significantly modified their acoustic criteria for distress judgments across the 10 trial blocks, 4) different listeners, while showing overall similarities in ratings of the 42 stimuli, also showed significant differences in acoustic criteria used in assigning the ratings of vocal distress, and 5) listeners who were both experienced and inexperienced in infant vocalizations coding showed high agreement in rating level of distress, but differed in the extent to which they relied on the different acoustic cues in making the ratings. The study provides clearer characterization of vocal distress expression in infants based on acoustic parameters and a new perspective on active adult perception of infant vocalizations. The results also highlight the importance of vibratory regime segmentation and analysis in acoustically-based research on infant vocalizations and their perception.